Validation of a new mortality risk prediction model for people 65 years and older in northwest Russia: The Crystal risk score. (July 2017) - Turusheva, Anna; Frolova, Elena; Bert, Vaes; Hegendoerfer, Eralda; Degryse, Jean-Marie
Highlights: A new risk prediction scores to predict mortality in older adults were developed. Model 1: low SPPB, Alow MAMA, low FEV1/Ht3, anemia. Model 2: low SPPB, low MAMA, low FEV1/Ht3, anemia +hCRP, hBNP. Model 2 has better predictive capacity for cardiovascular mortality than model 1. Both models were externally validated in another cohort of adults 80+. Abstract: Background: Prediction models help to make decisions about further management in clinical practice. This study aims to develop a mortality risk score based on previously identified risk predictors and to perform internal and external validations. Methods: In a population-based prospective cohort study of 611 community-dwelling individuals aged 65+ in St. Petersburg (Russia), all-cause mortality risks over 2.5 years follow-up were determined based on the results obtained from anthropometry, medical history, physical performance tests, spirometry and laboratory tests. C-statistic, risk reclassification analysis, integrated discrimination improvement analysis, decision curves analysis, internal validation and external validation were performed. Results: Older adults were at higher risk for mortality [HR (95%CI) = 4.54 (3.73–5.52)] when two or more of the following components were present: poor physical performance, low muscle mass, poor lung function, and anemia. If anemia was combined with high C-reactive protein (CRP) and high B-type natriuretic peptide (BNP) was added the HR (95%CI) was slightly higher (5.81 (4.73–7.14)) even after adjusting for age, sex and comorbidities. Our models were validated in an external population of adults 80+. The extended model had a better predictive capacity for cardiovascular mortality [HR (95%CI) = 5.05 (2.23–11.44)] compared to the baseline model [HR (95%CI) = 2.17 (1.18–4.00)] in the external population. Conclusion: We developed and validated a new risk prediction score that may be used to identify older adults at higher risk for mortality in Russia. Additional studies need to determine which targeted interventions improve the outcomes of these at-risk individuals.